Optimal in-feed amino acid ratio for broiler breeder hens based on deletion studies - Dorigam, J. C. P. [UNESP]; Sakomura, N. K. [UNESP]; Sarcinelli, M. F. [UNESP]; Goncalves, C. A. [UNESP]; Lima, M. B. de [UNESP]; Peruzzi, N. J. [UNESP] (Wiley-Blackwell, 2017)
An ideal amino acid ratio (IAAR) for breeder hens is needed for maximum nitrogen retention (NR) taking into account nitrogen deposition in body (NDB), feathers (NDF) and egg mass (NEM) to improve dietary protein efficiency. Thus, the aim of this study was to apply the deletion method to derive the IAAR for broiler breeder hens. The nitrogen balance trials were performed from 31 to 35weeks and from 46 to 50weeks. Twelve treatments with eight replicates and one hen per cage were used. A balanced diet (BD) was formulated to meet the requirement of all nutrients. The other diets were formulated diluting 55% of BD with corn starch and refilled with amino acids (AAs) and other ingredients, except the AA tested. Each trial lasted 25days. Feather losses, egg production and egg weight were recorded daily, and the samples were stored to further determine NEM and nitrogen in feather losses (NDFL). At the start and the end of each period, a group of birds were slaughtered to further determine NDB and NDF. The NR was calculated as the sum of NDB, NDF, NDFL, NEM and the nitrogen maintenance requirement (NMR). The deletion of valine greatly depressed the NR in peak production (31 to 35weeks) while the deletion of the isoleucine greatly depressed the NR of the hens from 46 to 50weeks of age. The percentual reduction in NR and the per cent of the AA to delete from the BD were used to calculate the AA requirement. The average IAAR was Lys 100, Met+Cys 86, Trp 23, Thr 80, Arg 113, Val 90, Ile 91, Leu 133, Phe+Tyr 108, Gly+Ser 94 and His 35. The IAAR was in line with the recommendation from the literature, validating deletion method with the advantages from a rapid and low-cost procedure.
Keywords: comparative slaughter; egg mass; fractional reduction; nitrogen retention; poultry